2023
DOI: 10.3389/fpls.2023.1137002
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth promoting potential of urea doped calcium phosphate nanoparticles in finger millet (Eleusine coracana (L.) Gaertn.) under drought stress

Abstract: Drought is a leading threat that impinges on plant growth and productivity. Nanotechnology is considered an adequate tool for resolving various environmental issues by offering avant-garde and pragmatic solutions. Using nutrients in the nano-scale including CaP-U NPs is a novel fertilization strategy for crops. The present study was conducted to develop and utilize environment-friendly urea nanoparticles (NPs) based nano-fertilizers as a crop nutrient. The high solubility of urea molecules was controlled by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 127 publications
0
6
0
Order By: Relevance
“…Similarly, Mishra et al [61] found increases in various growth-promoting parameters including shoot and root length, shoot and dry weight, shoot and root fresh weight, and leaf area when applying CaP-urea with particle size > 100 nm through spray deposition at a low concentration of NFs on a finger millet under drought and irrigated conditions. Also, a statistically significant difference was observed with a grain yield of wheat of more than 20% when zinc-and magnesium-doped hydroxyapatite NPs modified with urea were utilized [12], which fully agrees with our results.…”
Section: Reaction Of Spray-dispersed Phosphorus Nano-fertilizers With...mentioning
confidence: 90%
See 4 more Smart Citations
“…Similarly, Mishra et al [61] found increases in various growth-promoting parameters including shoot and root length, shoot and dry weight, shoot and root fresh weight, and leaf area when applying CaP-urea with particle size > 100 nm through spray deposition at a low concentration of NFs on a finger millet under drought and irrigated conditions. Also, a statistically significant difference was observed with a grain yield of wheat of more than 20% when zinc-and magnesium-doped hydroxyapatite NPs modified with urea were utilized [12], which fully agrees with our results.…”
Section: Reaction Of Spray-dispersed Phosphorus Nano-fertilizers With...mentioning
confidence: 90%
“…One of the pathways for the NPs to enter the plant is through the leaf stomata [61]. In the case of sunflower, the average stomata diameter corresponds to 28-30 µm [28].…”
Section: Reaction Of Spray-dispersed Phosphorus Nano-fertilizers With...mentioning
confidence: 99%
See 3 more Smart Citations